Introduction of an Advanced VIKOR method for Credit Rating of Customers of Banks - Mostafa Ekhtiari (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2012)
Now days, many internal banks of country experiment a kind of creditrisk, where can enumerate increasing non-performing loans of thebanks and not repayment problem of the central bank debts as itsresults. Therefore, to establish a system of credit risk management isnecessary and essential. The Five Cs of credit valid system is one ofthe rating systems of customers where can be considered for creditrisk management. In the other hand, existence of a suitable tool toestablish this system is necessary. The VIKOR method is one theefficient tools to rate feasible alternatives where can be used for ratingcredit of customers. In this paper, a method of advanced VIKOR willbe proposed which can present the optimal values of attributespreference weights in decision making process. To illustrate themethod proposed, a numerical example will be presented about creditrating problem of banks customers and the best feasible alternative togive facilities will be determined